Improving Brides-to-Be's Understanding of Reproductive Health to Strengthen Specific Interventions in Preventing Stunting - Eriyani, Theresia; Komariah, Maria; Hendrawati, Sri; Shalahuddin, Iwan (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Stunting is one of the main nutritional problems that is still a public health challenge in Indonesia. Specific interventions carried out from the preconception period, including reproductive health education for brides-to-be, play an important role in efforts to prevent stunting. Objective: This program aims to increase the bride-to-be's understanding of the importance of reproductive health in reducing the risk of stunting in children in the future. Method: This program is carried out in the form of a Real Work Lecture (KKN) program in Jelegong Village, Rancaekek District, Bandung Regency. Activities include an initial survey of the bride-to-be, reproductive health education, and health checks that include checking hemoglobin (Hb) levels, blood pressure, and body mass index (BMI). Evaluation is carried out through pre-test and post-test to assess the improvement of participants' understanding of the material provided. Results: The results of the evaluation showed a significant increase in the bride-to-be's understanding of reproductive health and stunting prevention. The average pre-test score of 77.4 participants increased to 94.1 in the post-test. In addition, the results of the health examination revealed that 47.8% of the bride-to-be had low hemoglobin levels, 34.7% had an abnormally low BMI, and 4.3% showed high blood pressure, which has the potential to increase the risk of pregnancy with suboptimal outcomes. Conclusion: Reproductive health education programs for brides-to-be have proven to be effective in increasing understanding and awareness of the importance of pre-pregnancy health preparation as a preventive measure against stunting. Further efforts, such as regular health monitoring and improved access to reproductive health services, are needed to strengthen the long-term impact of these interventions.